2021
DOI: 10.1063/5.0043511
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic infrared silicon photonics: The rise of (Si)GeSn semiconductors

Abstract: Si)GeSn semiconductors are finally coming of age after a long gestation period. The demonstration of devicequality epi-layers and quantum-engineered heterostructures has meant that tunable all-group IV Si-integrated infrared photonics is now a real possibility. Notwithstanding the recent exciting developments in (Si)GeSn materials and devices, this family of semiconductors is still facing serious limitations that need to be addressed to enable reliable and scalable applications. The main outstanding challenges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 63 publications
0
76
0
Order By: Relevance
“…As an additional path towards jointly improving maximum lasing temperature and threshold, which are driven by the directness and the quality of the material, respectively, strain engineering in suspended microdisk lasers allows increasing the material directness at moderate Sn contents. This is why we are currently investigating concepts for electrically pumped GeSn microdisk lasers [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an additional path towards jointly improving maximum lasing temperature and threshold, which are driven by the directness and the quality of the material, respectively, strain engineering in suspended microdisk lasers allows increasing the material directness at moderate Sn contents. This is why we are currently investigating concepts for electrically pumped GeSn microdisk lasers [40].…”
Section: Discussionmentioning
confidence: 99%
“…We are currently working on an electrically pumped suspended GeSn microdisk laser concept, a description of which can be found in Ref. [40].…”
Section: Device Descriptionmentioning
confidence: 99%
“…[2] Germanium (Ge) has been extensively explored for such a laser owing to its CMOS compatibility and near-direct bandgap configuration. [3,4] Among various approaches to achieve the bandgap directness, strain engineering [5][6][7][8][9][10][11][12][13] and tin (Sn) alloying [14][15][16][17] have been considered as the two most promising paradigms.…”
Section: Complementarymentioning
confidence: 99%
“…[17] For instance, it has been suggested that a large content of Sn increases the nonradiative recombination rate, thus leading to the reduction of internal quantum efficiency which influences the lasing threshold significantly. [17] In addition, the Sn alloying is typically accompanied by the compressive strain in the GeSn layer due to the large lattice mismatch between GeSn and Ge buffer layers. [15] Such compressive strain reduces the directness of GeSn, [28,29] thereby hindering the lasing performance.…”
mentioning
confidence: 99%
“…Limited by lattice matching for hetero-epitaxy, so far most of the α-Sn thin films have been grown on InSb instead of Si because the latter has a large lattice mismatch of ∼20%. Ge-rich GeSn alloys on Si have been extensively explored in optoelectronics community [11][12][13][14] , but high Sn composition SnGe alloys have been rarely studied experimentally since they are well beyond the solubility limit 2 . Furthermore, the thermal stability is also limited by the phase transition to β-Sn at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%